Implementation of Character Education in Building Attitude Tolerance Students Through Social Studies Learning in Class V SD Inpres 1 Kayumalue Taxi - Mila Tamrin; Lukman; Misnah (Kirana Publisher (KNPub), 2024)
The purpose of study This that is For know the implementation process education Characters in Class V of SD Inpres 1 Kayumalue Pajeko , which is related with attitude tolerance participant the students who are taught through social studies learning , as well as factors supporters and inhibitors in build attitude tolerance participant educate . Research This done Because see problems that occur among children namely in conditions and circumstances environment participant Educate today , who behaves not enough value existence difference with other friends so the occurrence case bullying and also behaving not enough polite towards someone more old . Research This is study Qualitative through approach descriptive , with technique collection the data through method Observation , Interviews , and Documentation . From the research that has been conducted by the author , based on results observation in class V SD Inpres 1 Kayumalue Taxi obtained presentation accuracy of data in the field related to the “ Implementation ” process education character in build attitude tolerance participant educate through